Interchangeability of Two Global Positioning System Devices for Measuring Player Movement in Rugby Union. - Oosthuizen, Jacobus J.; Rampinini, Ermanno; Bisschoff, Christo A.; Cockeran, Marike; Sparks, Martinique (Measurement in Physical Education & Exercise Science)
Global positioning systems (GPS) are widely used to monitor training loads, but the costs and wide variety of systems complicate longitudinal comparisons. We aimed to investigate the interchangeability of the more affordable Polar Team Pro against the more expensive Catapult Vector S7 GPS. Ten players, wearing both GPS units, each completed a series of standardized running drills totaling 290 exercise bouts for all participants: perimeter runs (10), box runs (100), linear sprints (120), and simulation runs (60). Concordance correlation coefficient (CCC) was used to determine the magnitude of agreement between the two GPS units. Findings indicated moderate to excellent agreement in velocity measures between the systems (CCC = 0.64–0.88), but poor agreement in distance (CCC = 0.17–0.40), acceleration (CCC = 0.23–0.44), and deceleration (CCC = 0.18–0.22) efforts. Practically, mean speeds (2.2–4.1 km/hr), distance (5.9–7.6 m), acceleration (1.5–3.1 efforts), and deceleration (1.5–3.6 efforts) need adjustment for comparison between Polar and Catapult systems.